Clinical and laboratory parameters associated with febrile seizure recurrence within the first 24 h: a ten-year cohort study - Castellazzi, Massimo Luca; La Vecchia, Adriano; Scali, Martina; Agostoni, Carlo; Di Pietro, Giada; Milani, Gregorio Paolo (Frontiers in Pediatrics, 2024)
Introduction We assessed clinical and laboratory parameters associated with early recurrence of febrile seizure in patients presenting at the Emergency Department with a first episode. Methods Case series of patients admitted to the emergency department with the first episode of febrile seizure for ten consecutive years. Exclusion criteria were focal features and prolonged duration (>15 min). Results We included 693 patients, 284 (41%) female. Median age of 20 (IQR 15–27) months. Fifty-two (8%) patients had a recurrence within 24 h. At univariate analysis, patients with recurrent seizures had higher use of antipyretics (88% vs. 74%, P = 0.03, OR 2.6, 95% CI: 1.1–7.7), higher median maximal body temperature (39.3 °C, IQR 38.9–39.9, vs. 38.9, IQR 38.4–39.3, P < 0.001, OR 2.3, 95% CI: 1.5–2.6) and presented with a lower proportion of respiratory tract infections (54% vs. 70%, P = 0.02) compared to patients without recurrence. A maximal body temperature equal to or higher than 39 °C was associated with a higher recurrence (11% vs. 4%, P < 0.001, OR 2.9, 95% CI: 1.6–5.6). Hyponatremia was not associated with a risk of recurrence. The multivariate analysis confirmed a direct association with body temperature (OR 2.3, 95% CI: 1.5–3.7, P < 0.001), and an inverse association with respiratory tract infections (OR 0.4, 95% CI: 0.2–0.9, P = 0.01), while antipyretic use was not correlated (OR 1.9, 95% CI: 0.8–5.2, P = 0.2). Conclusions High body temperature and respiratory tract infections were (directly and inversely) associated with recurrences. Consideration of these conditions might help for anticipating the probability of recurrence.